New Markers of Coronary Heart Disease with Old Myocardial Infarction: Certain Variants of Relative Length of Telomeric Repeats (London Journal of Medical and Health Research, 2024)
One of the possible factors in the occurrence of coronary heart disease with myocardial infarction is oxidative stress. Oxidative stress intensifies the formation of free radicals, causing defects in proteins and nucleic acids. This can lead to their partial or complete destruction. For example, the result of such destruction of DNA molecules may be a decrease in the length of telomeric repeats in the chromosomes of cells in coronary heart disease.Therefore, the aim of this work was to analyze the association of certain variants of the relative length of telomeric repeats with coronary heart disease with old myocardial infarction (CHD with MI).To measure the length of telomeric repeats, whole blood was collected, with the following DNA isolation from nuclear cells. The relative length of telomeric repeats was calculated based on the formula 2 to the power (-?Ct), where ?Ct = Ct of telomeres-Ct of albumin. In this case, Ct of telomeres is the threshold cycle of the telomeric repeat, and Ct of albumin is the threshold cycle of the albumin gene. The results of the relative length of telomeric repeats are presented as a percentage of the calibrator. DNA isolated from HeLa cell line was used as a calibrator.By measuring variants of the relative length of telomeric repeats in the studied samples, an association of coronary heart disease with myocardial infarction with VRLTR-46, VRLTR-49, VRLTR-51, VRLTR-53 and VRLTR-56 was detected. At the same time, 6 of 21 variants of the relative length of telomeric repeats (VRLTR-63, VRLTR-65, VRLTR-68, VRLTR-70, VRLTR-71 and VRLTR-73) had a protective effect in coronary heart disease with myocardial infarction.Therefore, in the present research work, we propose new markers of coronary heart disease with old myocardial infarction: certain variants of relative length of telomeric repeats (VRLTR).
Keywords: relative length of telomeric repeats; coronary heart disease with myocardial infarction; percentage of the calibrator; oxidative stress; protective effect; chromosomes.